Modification of Frozen Elephant Trunk Technique for Acute Type-A Aortic Dissection - A Case Report - Gupta, Saikat Das; Chanda, PK; Adhikary, DK (University Heart Journal, 2022)
Acute type-A aortic dissection (ATAAD) is a dreadfully fatal cardiovascular emergency. The mortality rate among medically treated patients is 50% within two days. Surgery is the gold standard and urgent surgical treatment is indicated for all patients, except for those who are moribund or severely comorbid. However, early mortality after operation remains high (9–25%). We hereby present a case of 22 years young, male, Marfan patient with a family history of ATAAD treated successfully by us at Square Hospital Ltd by modified Bentall’s procedure with total arch replacement with Frozen Elephant Trunk (FET) technique. University Heart Journal 2022; 18(1): 65-70